Understanding the transient behavior of the dew point evaporative cooler from the first and second law of thermodynamics. (15th September 2021) - Lin, Jie; Thu, Kyaw; Karthik, Somasundaram; Shahzad, Muhammad Wakil; Wang, Ruzhu; Chua, Kian Jon
Highlights: Large time constant of 400 s was observed for the dew point evaporative cooler. The slow transient response led to 13.8%–26.4% degradation in average performance. An air mixing process was identified via a modified model with exergy analysis. The exergy destruction at the dry channel entrance was critical due to air mixing. The sensitivities of the transient and steady-state performance were examined. Abstract: Owing to its high energy efficiency without using greenhouse gases, dew point evaporative cooling offers a desired solution for thermal management of electronic and electrical devices. This paper elucidates the transient behavior of a dew point evaporative cooler and its significant influence on the dynamic cooling performance. A large time constant (400 s) of the product air temperature was observed under a zero-state response, leading to a pronounced deviation of the time-average cooling performance below its steady state by 13.8%–26.4% over a long period (2500 s). To capture this phenomenon, a modified transient lumped parameter model and a new partial differential exergy model were developed. An air mixing process in the dry channel was identified to account for the slow cooler's transient responses. A detailed exergy analysis revealed that the specific exergy destruction at the dry channel entrance was above 400 W/kg, owing to the air mixing. This finding demonstrates that the transient behavior should be judiciously considered in the cooler design and optimization, together with the steady-state performance. Accordingly, a detailed sensitivity analysis of the cooler's objective variables is proposed to gain insights into the future improvement of the dew point evaporative cooler.